Reading “le grand livre de la Vie”:: Roch Carrier’s Les enfants du bonhomme dans la lune - Sheaffer-Jones, Caroline (Studies in Canadian Literature / Études en littérature canadienne, 2003)
The question of reading and writing occupies a central place in Roch Carrier's Les enfants du bonhomme dans la lune, and is also fundamental to the short essay "Comment j'ai écrit Les enfants du bonhomme dans la lune" which appears in the 1983 edition. In the text, reading and writing are understood as an interpretation of the surrounding world; the book which Sister Brigitte teaches the children to read is Life. All of the characters engage in a more or less insightful "reading" of Life, and several stories — as well as Carrier's explanation of these stories — reveal a search for that mysterious point at which the secret of the earth will be disclosed. In interpreting the world, either in his "fiction" or "non-fiction," Carrier has embarked on a difficult journey; there is no book in which the totality of Life is apparent — past, present, and future\ — and no text that is a transparent vision of the entire world.